2013
DOI: 10.1021/nn3053582
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Atomic Scale Patterning of Freestanding Monolayer Graphene at Elevated Temperature

Abstract: We show that by operating a scanning transmission electron microscope (STEM) with a 0.1 nm 300 kV electron beam, one can sculpt free-standing monolayer graphene with close-to-atomic precision at 600 °C. The same electron beam that is used for destructive sculpting can be used to image the sculpted monolayer graphene nondestructively. For imaging, a scanning dwell time is used that is about 1000 times shorter than for the sculpting. This approach allows for instantaneous switching between sculpting and imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
115
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 38 publications
1
115
0
Order By: Relevance
“…Theoretical studies show that an armchair ribbon will be semiconducting [66][67][68][69] and that a zigzag-edged ribbon is metallic with a current profile that peaks at the edges [66,[69][70][71]. Both armchair and zigzag nanoribbons have been proposed to present promising platforms for DNA sequencing in a large number of theoretical reports [72][73][74][75][76][77][78][79], and experimentalists have begun to explore this approach [80][81][82][83][84][85].…”
Section: Inplane Transport Of a Graphene Nanoribbon With A Nanoporementioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical studies show that an armchair ribbon will be semiconducting [66][67][68][69] and that a zigzag-edged ribbon is metallic with a current profile that peaks at the edges [66,[69][70][71]. Both armchair and zigzag nanoribbons have been proposed to present promising platforms for DNA sequencing in a large number of theoretical reports [72][73][74][75][76][77][78][79], and experimentalists have begun to explore this approach [80][81][82][83][84][85].…”
Section: Inplane Transport Of a Graphene Nanoribbon With A Nanoporementioning
confidence: 99%
“…Alternatively, chemical techniques that involve unzipping of carbon nanotubes or 'bottom up' assembly of ribbons with the use of molecular precursors have been used [89]. Freestanding graphene nanoribbons (of sub-10nm widths) were made using scanning transmission electron microscopy (STEM) to obtain narrow ribbons [82][83][84][85]. It was shown that when the graphene is heated to >600 • C, it can be sculpted with near atomic precision, while maintaining pristine defectfree graphene [84].…”
Section: Inplane Transport Of a Graphene Nanoribbon With A Nanoporementioning
confidence: 99%
See 1 more Smart Citation
“…They used an etching technique that selectively etches armchair edges, which produces hexagonal antidots with zigzag edges. Xu et al [21] have demonstrated that it is possible to create antidots with diameters down to 2 nm using a scanning transmission electron microscope. When subsequently heating the sample, the curved edges of the antidots were observed to reconstruct into armchair edges.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to produce GALs experimentally, including e-beam lithography [16][17][18], diblock copolymer templates [19][20][21], anodic aluminum oxide templates [22], nanosphere lithography [23] and nanoimprint lithography [24]. The antidots range in size between a few nanometers and several hundred nanometers, depending on the fabrication method.…”
Section: Introductionmentioning
confidence: 99%